Rapid high resolution melting assay to differentiate Streptococcus suis serotypes 2, 1/2, 1, and 14. Issue 4 (22nd January 2020) - Scherrer, Simone; Rademacher, Fenja; Spoerry Serrano, Nathalie; Schrenzel, Jacques; Gottschalk, Marcelo; Stephan, Roger; Landolt, Patricia
Abstract: This rapid high resolution melting (HRM) assay allows distinguishing between Streptococcus suis serotype pairs 2 and 1/2 as well as 1 and 14, respectively, based on a single‐nucleotide polymorphism within capsular polysaccharide synthesis gene cluster K. This assay is easy to implement and identifies potential zoonotic serotypes. Abstract : The designed high resolution melting assay allows to correctly differentiate Streptococcus suis serotype pair 2 and 1/2 or 1 and 14, respectively. The assay is based on a single‐nucleotide polymorphism within the capsular polysaccharide synthesis gene cluster K and enables a rapid identification of potential zoonotic serotypes.